2018
DOI: 10.1038/s41467-018-04376-5
|View full text |Cite
|
Sign up to set email alerts
|

A20 critically controls microglia activation and inhibits inflammasome-dependent neuroinflammation

Abstract: Microglia, the mononuclear phagocytes of the central nervous system (CNS), are important for the maintenance of CNS homeostasis, but also critically contribute to CNS pathology. Here we demonstrate that the nuclear factor kappa B (NF-κB) regulatory protein A20 is crucial in regulating microglia activation during CNS homeostasis and pathology. In mice, deletion of A20 in microglia increases microglial cell number and affects microglial regulation of neuronal synaptic function. Administration of a sublethal dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
127
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 59 publications
8
127
2
Order By: Relevance
“…A recent report has shown that A20 prevents inflammasomedependent arthritis through its ZnF7 ubiquitin-binding domain. As just discussed [59][60][61], this work showed that A20-deficient mice (A20 myc KO ) developed spontaneous arthritis that is critically dependent on RIPK1-RIPK3-MLKL-mediated necroptosis and that was accompanied by IL-1b and TNF-a release. Further studies on BMDMs further revealed that IL-1b release was mediated by RIPK3-dependent cell death (necroptosis) and that ZnF7 is critical for this function as LPS stimulation of BMDMs from mice with a mutated ZnF7 domain (A20 mZnF7/mZnF7 ) also induces the release of processed IL-1b (although at lower levels compared with A20-knockout cells) [63].…”
Section: Role Of Dubs In Canonical Nlrp3 Inflammasome Activationmentioning
confidence: 80%
“…A recent report has shown that A20 prevents inflammasomedependent arthritis through its ZnF7 ubiquitin-binding domain. As just discussed [59][60][61], this work showed that A20-deficient mice (A20 myc KO ) developed spontaneous arthritis that is critically dependent on RIPK1-RIPK3-MLKL-mediated necroptosis and that was accompanied by IL-1b and TNF-a release. Further studies on BMDMs further revealed that IL-1b release was mediated by RIPK3-dependent cell death (necroptosis) and that ZnF7 is critical for this function as LPS stimulation of BMDMs from mice with a mutated ZnF7 domain (A20 mZnF7/mZnF7 ) also induces the release of processed IL-1b (although at lower levels compared with A20-knockout cells) [63].…”
Section: Role Of Dubs In Canonical Nlrp3 Inflammasome Activationmentioning
confidence: 80%
“…Interestingly, IFNβ, the first line treatment for MS, is only effective in an NLRP3 inflammasome‐dependent EAE subtype, whereas NLRP3‐independent EAE could not be reversed by IFN‐β therapy (Inoue et al , , ). We recently provided direct genetic evidence for the relevance of inflammasome signaling in microglia and border‐associated macrophages during EAE (Voet et al , ). The anti‐inflammatory protein A20 has been shown to negatively regulate NLRP3 inflammasome activation (Vande Walle et al , ), and deletion of A20 in microglia and CNS macrophages exacerbated EAE in mice due to NLRP3 hyperactivation that resulted in increased IL‐1β secretion and CNS inflammation (Voet et al , ).…”
Section: Inflammasome Activation In Multiple Sclerosis and Experimentmentioning
confidence: 99%
“…We recently provided direct genetic evidence for the relevance of inflammasome signaling in microglia and border‐associated macrophages during EAE (Voet et al , ). The anti‐inflammatory protein A20 has been shown to negatively regulate NLRP3 inflammasome activation (Vande Walle et al , ), and deletion of A20 in microglia and CNS macrophages exacerbated EAE in mice due to NLRP3 hyperactivation that resulted in increased IL‐1β secretion and CNS inflammation (Voet et al , ). CNS‐intrinsic inflammasome activation was further reported in another study that showed caspase‐1‐ and GSDMD‐mediated pyroptosis in microglia, as well as in myelin‐forming oligodendrocytes in the CNS of MS patients and EAE mice (Mckenzie et al , ).…”
Section: Inflammasome Activation In Multiple Sclerosis and Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…A20 deubiquitinase, a negative regulator of NF‐κB, has been reported to play a critical role in activation of microglia and inhibition of inflammasome‐dependent neuroinflammation through blocking ubiquitination of pro‐IL‐1β . However, A20 does not effectively inhibit other inflammasomes, such as AIM2 and NLRC4 .…”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%